The continuity of Wittgenstein's thought - Koethe, John, 1945- (Cornell University Press, 1996)
Ludwig Wittgenstein's philosophical work is informed throughout by a particular broad theme: that the semantic and mentalistic attributes of language and human life are shown by verbal and nonverbal conduct, but that they resist incorporation into the ...